Combination of a novel electrode material and artificial mediators to enhance power generation in an MFC - Taskan, Ergin; Ozkaya, Bestamin; Hasar, Halil (IWA PUBLISHING, 2015)
This study focuses on two main aspects: developing a novel cost-effective electrode material and power production from domestic wastewater using three different mediators. Methylene blue (MB), neutral red (NR) and 2-hydroxy-1,4-naphthoquinone (HNQ) were selected as electrode mediators with different concentrations. A tin-coated copper mesh electrode was tested as anode electrode. Maximum power density of the microbial fuel cell (MFC) with 300 mu M MB was 636 mW/m(2). Optimal mediator concentrations with respect to the achieved maximum power output for MB, NR and HNQ were 300 mu M, 200 mu M and 50 mu M, respectively. The results demonstrate that tin-coated copper mesh showed a higher biocompatibility and electrical conductivity.
Keywords: microbial fuel cell; mediator; power output; internal resistance; MICROBIAL FUEL-CELLS; ELECTRICITY-GENERATION; METHYLENE-BLUE; NEUTRAL RED; PERFORMANCE; ANODE; Engineering; Environmental Sciences & Ecology; Water Resources